When the Nerds Go Marching In How Digital Technology Moved from the Margins to the Mainstream of Political Campaigns - Gibson, Rachel K. (Oxford Studies in Digital Politics, 2020)
When the Nerds Go Marching In shows how digital technology has moved from the margins to the mainstream of campaign and election organization in contemporary democracies. Combining an extensive review of existing literature and comparative data sources with original survey evidence and web content analysis of digital campaign content across four nations-the United Kingdom, Australia, France, and the United States-the book maps the key shifts in the role and centrality of the internet in election campaigns over a twenty-year period. The chapters reveal how these countries have followed a four-phase model of digital campaign development which begins with experimentation, and is followed by a period of standardization and professionalization. Subsequent phases focus on increasingly strategic activities around the mobilization of activists and supporters, before switching to micro-targeted mobilizing of individual voters. The changes are mapped over time in each country from the perspective of both the campaigners (supply side), and that of voters (demand side), and the four nations are compared in terms of how far and fast they have moved through the developmental cycle. As well as providing the most comprehensive narrative charting the evolution of digital campaigning from its inception in the mid-1990s, the book also offers important insights into the national conditions that have been most conducive to its diffusion. Finally, based on the findings from the most recent phase of development, the book speculates on the future direction for political campaigns as they increasingly rely on digital tools and artificial intelligence for direction and decision-making during elections.